Proposed bay' al-salam with takaful and value chain model for financing agriculture in Kano State, Nigeria - Atah, Ummi Ibrahim
The growth and development of agricultural sector of Nigeria is seriously undermined due to pathetic challenges that debilitate the sector. The most acute challenge that bedeviled the sector is the financing challenge, which becomes detrimental to the farmers, society and economy in general. This situation is confirmed by the recent recession the country has fallen into, which exacerbate poverty, unemployment, starvation and food insecurity. Consequently, it is imperative to carry out a practical empirical research to find out the major problems thereby coming up with a viable model that will serve as a solution to improve the agricultural growth and development of Nigeria. This study aims to investigate the major challenges facing the agricultural sector, examines the dimension of financing challenges facing farmers, propose a viable model of financing farmers through seeking the stakeholder's perception with regard to acceptability of the proposed model. To explore rich data for accurate analysis, the study used pragmatic as a world view and adopts exploratory sequential mixed method, where both the qualitative and quantitative method were utilized. This covers semi-structured interview with 7 experts by using purposive sampling and thematic analysis and distribution of 300 questionnaires to grass root farmers using multistage cluster sampling and analysis through descriptive statistics and factor analysis. The study findings revealed that the major challenges facing agricultural sector includes inadequate financing, risk issues, poor logistics, ineffective government policies and programmes, inadequate technical know-how, inadequate infrastructural facilities, inadequate modern input facilities, lack of incorporating value chain and lastly corruption.The study findings also revealed the most disturbing financing challenges from the qualitative phase to include inadequate financing, religiosity, higher charges and collateral issue. The quantitative findings support the qualitative one as inadequate financing has the highest eigenvalue of 7.655, with the religiosity issue following with eigenvalue of 2.058. The third is credit eligibility with eigenvalue of 1.604, while the fourth factor is Government policies and programmes with eigenvalue 1.485. The study also found that all the agricultural stakeholders are willing to accept the proposed model because of the anticipated prospects such as economic benefit which includes increasing access to finance, employment creation, poverty reduction, improved food production, other sources of profit to financial institutions, enhancing Islamic values, facilitating the use of other Islamic banking product and lastly risk minimization. However, poor awareness, non-expert involvement, wrong selection of farmers, untimely disbursement of financing, poor monitoring and evaluation and not taken expert advice into practice are envisaged challenges that could hinder its successful implementation. Hence, it is suggested by the respondents that expert involvement, giving financing to actual farmers, timely disbursement of financing, proper monitoring and evaluation, strict adherence to expert advice, awareness campaign and educational programmes are the key to the successful implementation of the model.